Ocho neoplasias primarias metacrónicas en paciente mujer adulta mayor - Purizaca-Rosillo, N (2022)
Multiple primary neoplasms (MPN) are defined as 2 or more primary malignant tumors of different origin in the same individual. The cause of MPN has not been identified in all cases, however, it may be due to environmental factors, lifestyles and/or genetic factors. We present the case of a patient who has had eight neoplasms (five malignant and three benign) that have been successfully treated and who is currently undergoinf controls, with no evidence of disease recurrence or any other de novo neoplasm.